HYPOANDROGEN CONDITION AND CARDIOVASCULAR DISEASES: ACTUAL QUESTIONS OF COMORBIDITY IN CLINICAL PRACTICE - G. G. Sharvadze; D. G. Kurbatov; E. A. Poddubskaya; M. N. Mamedov (Рациональная фармакотерапия в кардиологии)
The correlation of age-dependent reduction in sex hormones level and changes of cardiovascular system in men was shown recently. High prevalence and various clinical features of age-dependent hypogonadism demands to know diagnostics and management of patients with these disorders. Up to date data about changes of cardiovascular system related to androgen hormone levels reduction are presented. They should help in understanding of pathogenesis of many metabolic and clinical changes. Active attention to the problem of age-dependent hypogonadism, knowledge of organism functions in men with low androgen levels will help to optimize treatment, to avoid of mistakes in patient management, to reduce a risk of severe diseases and finally to improve quality of life and life expectancy of these patients.